One Algorithm to Cipher Messages in Columnar and Fixed Period-d Transposition Cipher - Jassim, J.N.; Muhsen, H. J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
One of ciphering systems depends on transposition of letters in plain text to generate cipher text. The programming of transposition depends mainly on 2-dimension matrix in either methods but the difference is in columnar .We print columns in the matrix according to their numbers in key but in the fixed, the cipher text will be obtained by printing matrix by rows.